Energy Homeostasis and Abnormal RNA Metabolism in Amyotrophic Lateral Sclerosis - Liu, Yu-Ju; Tsai, Po-Yi; Chern, Yijuang (Frontiers in Cellular Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease that is clinically characterized by progressive muscle weakness and impaired voluntary movement due to the loss of motor neurons in the brain, brain stem, and spinal cord. To date, no effective treatment is available. Ample evidence suggests that impaired RNA homeostasis and abnormal energy status are two major pathogenesis pathways in ALS. In the present review, we focus on recent studies that report molecular insights of both pathways, and discuss the possibility that energy dysfunction might negatively regulate RNA homeostasis via the impairment of cytoplasmic-nuclear shuttling in motor neurons and subsequently contribute to the development of ALS.